CONTEXTUALIZATION OF ISLAMIC LAW FOR LOCAL MUSLIM MINORITIES: THE TRADITION OF BERAS KAFARAT IN DEATH RITUALS IN KERINCI, JAMBI, FROM THE PERSPECTIVE OF AL-‘URF - Bayu Arif Mahendra; Asmawi; Muhamad Arief Al Hakim (Sahaja: Journal Sharia and Humanities, 2025)
This study examines the beras kafarat tradition in Tebing Tinggi, Kerinci Regency, Jambi, Indonesia, highlighting its religious and social significance in death-related rituals using the al-‘urf approach within the scope of the contextualization of Shari'a, considering the limited Muslim population. This tradition serves as an atonement for the deceased who may have neglected religious obligations, fostering solidarity in the community and a sense of unity amidst the pressures of modernization. Using a qualitative approach, data were collected through interviews and observations, involving local residents and ninik mamak (community elders) for a deeper understanding. The findings reveal that the beras kafarat tradition is not only a religious act but also provides emotional comfort to grieving families, alleviating the social pressures they face after the death of a loved one. Furthermore, this study emphasizes the role of the younger generation in preserving this tradition, as their involvement is crucial for its continuity. Adapting traditional practices to suit the modern context without losing cultural and religious values is also important. Overall, the sustainability of the beras kafarat tradition relies on educational and communal efforts to preserve this cultural heritage. This study aims to enhance understanding of the interaction between tradition, religion, and social dynamics in Indonesian Muslim society and to encourage dialogue on the importance of preserving traditions amidst societal change.